Risk factors for non-optimal breastfeeding practices in low birth weight infants - Ekawaty L Haksari; Setya Wandita; Yustivani Yustivani (Indonesian Pediatric Society, 2010)
Background Low birth weight infants are ongoing problems sincethey are likely to have high risks of morbidity, mortality andfeeding problems. American Academy of Pediatrics recommendsbreastfeeding practice for infants with low birth weight, yet someproblems have occured.Objective To determine risk factors for non-optimal breastfeedingpractices in low birth weight infants.Methods In this historical cohort study we included mothers with6-month-old infants, single birth with weight of2000-2499 gramsand the pregnancy period of 2:: 34 weeks, and excluded motherswith infants who had a major congenital disorder, labioschizis,labiognatopalatoschizis, or history of admission in NICU. Datawere collected using standard longitudinal surveillance form forbreastfeeding mothers. Analyses were performed using chi-squaretest and logistic regression.Results The percentage of low birth weight infants breastfedoptimally were 42.7%. Working mothers presented the highestrisk for non-optimal breastfeeding. The onset of lactation formore than 6 hours was the second factor (81.8%). The resultsof multivariate logistic regression analysis showed that motherswho worked (RR 2.79; 95% CI 1.84 to 4.23) and onset lactationof more than 6 hours (RR 2.34; 95% CI 1.57 to 3.50) were therisk factors for non-optimal breastfeeding practices in low birthweight infants.Conclusion Mother's working status and onset of lactationfor more than 6 hours were the risk factors for non-optimalbreastfeeding in low birth weight infants.